PENGEMBANGAN PROGRAM LAYANAN BIMBINGAN DOSEN PENASEHAT AKADEMIK DI UIN SUSKA RIAU - Muslim Afandi (Lembaga penelitian dan pengabdian kepada masyrakat, 2012)
One of its appearance assumption observational / this writing for example that counselling guidance not only been applied at secondary school, but clearing away comes up college, since on its reality services counselling guidance can’t be came to pieces deep entire education and learning process. UIN Suska Riau notably Tarbiyah’s faculty and teachership is one college institute that haven’t had guidance independent institute counselling and this service still integrated with duty assignment that at bellyband by Academic Advisor lecturer so a lot of constraint that is met. Realita such a inspire writer to get collaboration with PA’s lecturer arrange research to develop guidance service program that corresponds to condition and college student the need via action research. Via procedure that corresponds to character action reserch , PA’s writer and lecturer successful formulate hipotetik’s program services PA’s lecturer at a swoop gets commitment for mensosialisasikan and empowers it in day-to-day task as consequence to lap over it kolaboritif ’s of programmer